Rebleeding in aneurysm after rectal enema: Re‐emphasis on careful subarachnoid hemorrhage management - Suraj Shrestha; Akash Raut; Sushan Homagain; Gopal Sedain; Rupesh Ramtel (Clinical Case Reports, 2021)
Abstract Rebleeding in an aneurysmal subarachnoid hemorrhage (SAH) is catastrophic with high mortality and grave outcome. Meticulous management of SAH patients and the prevention of activities that might increase the chances of rebleeding are life‐saving.